Efektivitas Penggunaan Pop Up Book Sebagai Media Pembelajaran Terhadap Peningkatan Hasil Belajar Biologi Siswa - Andi Khaerunnisa (CV. Insight Publisher, 2023)
This research is quantitative research with Pre-Experimental method and One-Group Pretest-Posttest Design which aims to determine the effectiveness of using Pop Up Books as a medium of learning for students' biology learning outcomes. Sampling was done by using saturated sampling technique, the sample in this study were 19 students of class XI IPA 2 SMA DDI Maros. In this study, only one class was involved as an experimental class who learned to use Pop Up Book media. The instrument used was a student activity observation sheet and a multiple choice test of 20 validated questions. The research data were analyzed descriptively and inferentially. Based on the results of data analysis, the average of the pretest learning outcomes was 41.32 and the posttest was 79,21 with the percentage of students who completed 79%. And the results of observing student activities have an average value of 73,15% including good categories. The results of the N-Gain test showed an increase in student biology learning outcomes of 0.6434 in the medium category. The data in this study were tested for normality using the Shapiro-Wilk test and the One Sample T Test t test obtained sig 0.000 <0.05. The results of this study indicate that the use of Pop Up Books is effective as a learning medium for the biology learning outcomes of class XI science students at SMA DDI Maros on the material of the human reproductive system.